Implementasi Pengelolaan Aset Daerah pada BPKAD Kabupaten Bogor Tahun 2022 - Lewina Sulistiawati; Hurriyaturrohman Hurriyaturrohman; Muhamad Nur Rizqi (Journal on Education, 2023)
This research aims to determine the analysis of regional asset management at BPKAD Bogor Regency in 2022 and the obstacles that occur in its implementation. Data collection techniques using observation, interviews and documentation. The results of the research show that the regional asset management process in BPKAD Bogor Regency is in accordance with Permendagri No.19 of 2016 and the activities for recording reports and classifying fixed assets have followed the applicable provisions in PSAP No.07 for fixed assets in their manufacture, namely in the utilization of fixed assets that can used within a period of 1 year or 12 months. Obstacles in the regional asset management process at BPKAD Bogor Regency are, firstly, Human Resources which do not match the workload with the number of human resources and the lack of human resources who have expertise, knowledge about control, depreciation and control of regional assets in the field of asset management, secondly, there is limited time for asset recording which is only effective for 6 (six) months, thirdly the technology is still manual using Excel